Fifty Years of Retracted Medical Publications From 1975 to 2024: A Comprehensive Analysis of Trends, Reasons, and Countries Using the Retraction Watch Database - Okyay, Ramazan Azim; Kocyigit, Burhan Fatih; Qumar, Ainur B.; Yessirkepov, Marlen; Sumbul, Hilmi Erdem (Journal of Korean medical science, 2025)
Background: Scientific medical research has progressed tremendously during the last 50 years, but concerns about research integrity, publishing ethics, and retraction trends have grown. Retractions are essential for revising the scientific record and maintaining credibility, yet an extensive long-term assessment of retracted medical publications is limited. Methods: We performed a descriptive analysis of 50 years of retracted medical publications from the Retraction Watch Database. Data were refined to encompass solely medicine-related retractions, omitting corrections, expressions of concern, and reinstatements. We classified retraction reasons into 68 categories, emphasizing the top 10 most frequently encountered reasons. Temporal trends were evaluated employing semi-logarithmic linear regression models. The geographical distribution and journal-specific retractions were also examined. Results: An analysis was conducted on 16,041 retracted medical documents from 1975 to 2024. The leading reasons for retraction included data concerns (31.47%), fraud (11.37%), peer review issues (11.21%), referencing issues (7.54%), and ethical violations (7.09%). The highest number of retractions was noted in Computational and Mathematical Methods in Medicine (5.91%), Journal of Healthcare Engineering (5.85%), and Evidence-Based Complementary and Alternative Medicine (4.36%). Approximately 45.28% of retracted papers included at least one author from China, followed by the United States and India. The medical subfields most impacted were oncology (19.87%), cardiovascular medicine (15.62%), and pharmacology (14.49%). Temporal analysis indicated a steady rise in retractions, with data concerns and fraud doubling typically every 5.5 and 5.2 years. Conclusion: The rising amount of retractions underscores heightened scrutiny and enhanced detection techniques while highlighting ongoing research integrity issues. Data integrity, fraudulent activities, and compromised peer review are significant issues. Fortifying editorial policies, augmenting transparency, and bolstering research ethics education are essential for reducing misconduct and maintaining the integrity of medical papers. KCI Citation Count: 0